Sox transcription factors require selective interactions with Oct4 and specific transactivation functions to mediate reprogramming - Aksoy, Irene (2014)
The unique ability of Sox2 to cooperate with Oct4 at selective binding sites in the genome is critical for reprogramming somatic cells into induced pluripotent stem cells (iPSCs). We have recently demonstrated that Sox17 can be converted into a reprogramming factor by alteration of a single amino acid (Sox17EK) within its DNA binding HMG domain. Here we expanded this study by introducing analogous mutations to 10 other Sox proteins and interrogated the role of N-and C-termini on the reprogramming efficiency. We found that point-mutated Sox7 and Sox17 can convert human and mouse fibroblasts into iPSCs, but Sox4, Sox5, Sox6, Sox8, Sox9, Sox11, Sox12, Sox13, and Sox18 cannot. Next we studied regions outside the HMG domain and found that the C-terminal transactivation domain of Sox17 and Sox7 enhances the potency of Sox2 in iPSC assays and confers weak reprogramming potential to the otherwise inactive Sox4EK and Sox18EK proteins. These results suggest that the glutamate (E) to lysine (K) mutation in the HMG domain is necessary but insufficient to swap the function of Sox factors. Moreover, the HMG domain alone fused to the VP16 transactivation domain is able to induce reprogramming, albeit at low efficiency. By molecular dissection of the C-terminus of Sox17, we found that the β-catenin interaction region contributes to the enhanced reprogramming efficiency of Sox17EK. To mechanistically understand the enhanced reprogramming potential of Sox17EK, we analyzed ChIP-sequencing and expression data and identified a subset of candidate genes specifically regulated by Sox17EK and not by Sox2.